Ursodeoxycholic Acid (UDCA) Promotes Lactate Metabolism in Mouse Hepatocytes through Cholic Acid (CA) - Farnesoid X Receptor (FXR) Pathway - Wang, Lu; He, Huai-Wu; Zhou, Xiang; Long, Yun (Current Molecular Medicine, 2020)
Background: Persistent hyperlactatemia is associated with greater mortality in shock. Liver is the main site of lactate metabolism. Method: In the first part, freshly isolated hepatocytes were incubated in 10% fetal bovine serum William's E medium supplemented with 10 mM lactate. Cells were then exposed to 100 μM ursodeoxycholic acid (UDCA), with no addition (control) for 2, 4, 6, 8 h. In the second part, hepatocytes were treated with Silencer select siRNA targeting FXR or scramble siRNA. The siRNA treatment was repeated twenty four hours later, and the cells were used in the experiments twenty-four hours after the second treatment. Then hepatocytes were incubated in 10% fetal bovine serum William's E medium supplemented with 10 mM lactate. Cells were then exposed to 100 μM UDCA for 2, 4, 6, 8 h. Lactate concentration was determined by ABL80 automatic blood gas analyzer. Results: UDCA increased ability of hepatocytes to remove lactate. After the knockdown of FXR, effects caused by UDCA were weakened. Conclusion: These results demonstrate that UDCA promotes lactate metabolism in mouse hepatocytes through CA-FXR pathway.
Keywords: cholic acid